Multicriteria in Bank Loan Portfolio Management - Irena Mačerinskienė; Laura Ivaškevičiūtė; Justas Babarskas (Ekonomika, 2004)
This paper is devoted to a review of the Multicriteria Framework of financial decisions of bank loan portfolio management as a financial model supporting financial decision-making, which builds pointed models taking into account the peculiarities of a problem. The goal here is to bridge the gap between decision-making disciplines of financial economics and the need for adequate decision support. Finance has traditionally recognized the two-objective situation of risk versus return, with the fundamental goal of wealth maximization. However, not well known are the new ways of approaching financial problems when three or more criteria exist. The modern portfolio management approach involves complex goals where they interact with one another; each has its own possible interpretation of wealth maximization, subjects to concern about risk, safety, liquidity, profitability, social responsibility, environmental protection, employee welfare, and so on. Consequently, it may well be appropriate to pursue a multiple objective approach to many financial decision-making problems. This article is concentrated upon building up a model with multicriteria analysis that provides financial decision makers and analysts with a wide-range methodology well suited to the complexity of modern bank loan portfolio management decision-making.